2019
DOI: 10.1073/pnas.1814723116
|View full text |Cite
|
Sign up to set email alerts
|

Leading a meaningful life at older ages and its relationship with social engagement, prosperity, health, biology, and time use

Abstract: SignificanceRatings of the meaningfulness of life have been adopted in UK national surveys and are advocated internationally. This study demonstrates the value of a simple rating of the extent to which people feel that the things they do in life are worthwhile, by documenting positive associations with social relationships and broader social engagement, economic prosperity, mental and physical health, biomarkers, health-related behaviors, and time use. These associations were observed both cross-sectionally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
141
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(162 citation statements)
references
References 20 publications
18
141
2
1
Order By: Relevance
“…Differences in the detail with which health was assessed may be responsible for this discrepancy. It is striking that the majority of biomarkers did not predict changes in worthwhile ratings, which suggests that the cross-sectional associations previously observed may be a result of the impact of leading a meaningful life on biology rather than vice versa 17 . Nevertheless, some research indicates that interventions enhancing eudaimonic wellbeing promote biological processes such as increased expression of antiviral and antibody-related gene expression 44 .…”
Section: Determinants Of Changes In Worthwhile Ratings Over Two Yearsmentioning
confidence: 78%
See 1 more Smart Citation
“…Differences in the detail with which health was assessed may be responsible for this discrepancy. It is striking that the majority of biomarkers did not predict changes in worthwhile ratings, which suggests that the cross-sectional associations previously observed may be a result of the impact of leading a meaningful life on biology rather than vice versa 17 . Nevertheless, some research indicates that interventions enhancing eudaimonic wellbeing promote biological processes such as increased expression of antiviral and antibody-related gene expression 44 .…”
Section: Determinants Of Changes In Worthwhile Ratings Over Two Yearsmentioning
confidence: 78%
“…In our previous study, we demonstrated that higher ratings of doing worthwhile things in life were associated with a wide range of social, health, and behavioural outcomes 4 years later, independent of baseline levels of these variables 17 . The present analyses add to these findings in showing that over and above baseline worthwhile ratings, increases in ratings over a 2 year period were associated with the same set of outcomes at 4 years.…”
Section: Determinants Of Changes In Worthwhile Ratings Over Two Yearsmentioning
confidence: 81%
“…Regardless of migration background, social interactions with family and friends have been shown to be strongly linked to better mental health for the older population (Burholt et al, 2018;Cohen, 2004;Cramm et al, 2013;House et al, 1988;Shaw et al, 2007;Steptoe & Fancourt, 2019;Stokes & Moorman, 2018), consistent with the idea of linked lives (Mortimer & Shanahan, 2007). Regular social engagement with friends and family is essential to mental health for people of all ages (House et al, 1988), but the relationship of the two intensifies near retirement age or empty nest (Cattan et al, 2005) due to the reshuffling of balance toward personal life as work and child rearing obligations subside.…”
Section: For Better or For Worse Mental Health? The Role Of Social Nementioning
confidence: 62%
“…There is room for further research on this question in relation to a range of samples, and timeframes, and using appropriate control samples. This is especially the case in light of a recent longitudinal study of 7,305 older adults which revealed that people who believe their life is filled with worthwhile activities (such as involvement in civic society, cultural activities and volunteering) experience greater wellbeing and healthier ageing (Steptoe & Fancourt, 2019).…”
Section: Priority Questions For Group Singing Researchmentioning
confidence: 99%